Estrategias metodológicas para el desarrollo del hábito lector en los estudiantes del quinto año de educación general básica de la escuela Dr. Edison Calle Loaiza, del barrio Daniel Álvarez, de la ciudad de Loja, período académico 2014- 2015 - Rivilla Pereira, Lizbeth Katherine (2016)
This research titled RULES OF CONDUCT FOR IMPROVED INTRA-CLASS coexistence in fourth graders PARALLEL TO SCHOOL EDUCATION BACKGROUND EDISON CALLE LOAIZA CITY OF LOJA. PERIOD 2014- 2015, had as its overall objective to apply the rules of behavior to improve intra-class coexistence. The research was pre-experimental and cross-sectional, explanatory character and field; in which methods were used: synthetic, inductive-deductive analytic and statistical-descriptive; the techniques used and the recruitment and survey through its instrument the questionnaire applied to 17 students and a teacher. After obtaining the results showed that most students did not meet the performance standards set out in the classroom, which generated a conflictive coexistence, showing aggressive actions and little companionship. Since the implementation of the workshops was succeeded in establishing student assertive behaviors, which allowed increase fellowship and strengthen the practice of values in the classroom. Thus it was concluded that the application of rules of behavior in the classroom, proved to be one of the most efficient ways to achieve good coexistence through compliance intra behavior. Therefore the teacher is recommended strategies and innovative activities that allow the student to live among peers, putting into practice the values inside and outside the classroom.